Design and evaluation of vaccines for the control of the etiological agent of East Coast fever - José de la Fuente; Isidro Sobrino; Margarita Villar (Parasites & Vectors)
Abstract East Coast fever is a tick-borne theileriosis caused by Theileria parva, a protozoan parasite with the primary vector being the tick Rhipicephalus appendiculatus. This disease poses significant challenges in sub-Saharan Africa, leading to severe economic losses by causing the death of over one million livestock annually. Current control measures include vector control with acaricides and the “infection and treatment” method, which involves immunization with live sporozoites of the pathogen and treatment with long acting oxytetracycline. Despite their effectiveness, these methods face scalability and usability issues, necessitating the development of new prevention strategies, particularly in the field of vaccines for the effective and sustainable control of East Coast fever. In this primer focus, East Coast fever serves as a case study to highlight recent concepts and advancements in tick and tick-borne disease vaccine research. Vaccine design and evaluation processes are reviewed, encompassing the utilization of omics datasets and knowledge on vectors and pathogens, and exploring new design methods, such as quantum vaccinomics and messenger RNA (mRNA)-based vaccines. Key limitations and areas requiring further research are addressed, including insufficient understanding of host–pathogen molecular interactions, the impact of post-translational modifications, and vaccine efficacy variability across different trials. Additionally, new research objectives are proposed to address East Coast fever but with possible impact on other tick-borne diseases. It includes advancing knowledge on tick–pathogen–host molecular interactions, studying tick microbiota, developing novel design approaches, such as combining tick and pathogen epitopes in chimeric vaccines (exemplified by the q38–p67c case), and exploring new immunological enhancers and delivery platforms. Graphical Abstract